2015
DOI: 10.1186/s12883-015-0318-0
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making under explicit risk is impaired in multiple sclerosis: relationships with ventricular width and disease disability

Abstract: BackgroundDecision-making is an essential function of everyday life. Decision-making under explicit risk requires developing advantageous decision strategies based on fixed outcomes (e.g., probabilities of winning or losing a bet). Decision-making and its neural substrates have been rarely studied in MS. We expected performance in decision-making under risk to be lowered in MS patients, and negatively correlated with disease-related disability, cognition, and ventricular width.MethodsThree groups were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 63 publications
1
19
0
Order By: Relevance
“…Importantly, previous studies found abnormal decision-making related behaviours in MS patients 8-17 . However, it is unclear if and to what extent do these abnormal behaviors contribute to the deterioration in the quality of life of MS patients and how are they related to other dimensions of the disease such as disability, cognition or social aspects.…”
Section: Introductionmentioning
confidence: 83%
“…Importantly, previous studies found abnormal decision-making related behaviours in MS patients 8-17 . However, it is unclear if and to what extent do these abnormal behaviors contribute to the deterioration in the quality of life of MS patients and how are they related to other dimensions of the disease such as disability, cognition or social aspects.…”
Section: Introductionmentioning
confidence: 83%
“…Multiple Sclerosis (MS) is a chronic inflammatory demyelinating disorder of the central nervous system [1,2]. Around 85% of all people with MS are diagnosed with relapsing remitting MS RRMS [3,4] characterised by episodes of neurological dysfunction followed by complete or partial remission often leading to a stepwise increase in residual impairments [1,5,6].. The last decade has seen a rapid increase in the number of licensed disease modifying treatments (DMTs) for people with RRMS (PwRRMS).…”
Section: Introductionmentioning
confidence: 99%
“…Greater understanding of how MS affects risk evaluation is also becoming increasingly important. Previous work has suggested that some people with MS, particularly those with secondary progressive MS or with greater physical or cognitive impairment, may show decision-making deficits, and so may struggle, for example, to adjust to different levels of risk (Kleeberg et al, 2004;Muhlert et al, 2015;Radomski et al, 2015). This may have implications for adherence, as those who fail to adhere to DMTs tend to devalue treatment efficacy and inflate treatment risks (Bruce et al, in press).…”
mentioning
confidence: 97%